2014
DOI: 10.1210/jc.2013-3199
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Infant Weight Gain and Risk for Nonalcoholic Fatty Liver Disease in Early Adulthood

Abstract: Accelerated gain in weight for length in the first 3 months of life is associated with a higher risk for NAFLD in early adulthood, whereas small size at birth is not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
4
36
0
1
Order By: Relevance
“…The data of the participants were compared with the data of 268 young adults born at full term (PROGRAM study) [9]. Both cohorts had similar in- and exclusion criteria and measurements and were from the same research center, but they had a different gestational age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data of the participants were compared with the data of 268 young adults born at full term (PROGRAM study) [9]. Both cohorts had similar in- and exclusion criteria and measurements and were from the same research center, but they had a different gestational age.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group showed that young adults who were born at full term and underwent accelerated weight gain during infancy had an increased fatty liver index (FLI), a measure of NAFLD in early adulthood [9]. While the gold standard for determining NAFLD is liver biopsy, the FLI is widely used and has recently been validated for identifying NAFLD in a large population-based study [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrauterine growth retardation (IUGR) is associated with the development of clinical manifestations of the MetS and increased cardiovascular risk in adulthood [10] and is a strong risk factor for NAFLD since childhood [17,18]. We had previously shown the association of paediatric NAFLD with IUGR; the prevalence of SGA in children with NAFLD resulted about four times higher compared to the average percentage of the hospitalized children [18].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the "foetal insulin hypothesis" suggests that alterations in insulin sensitivity and secretion in newborns with intrauterine growth reduction are genetically determined and independent of the intrauterine environment [16]. In any case, at birth, when nutrient availability is higher, this "greedy" metabolism may cause fast weight gain and 6 fat accumulation predisposing children with IUGR both to MetS and NAFLD in adulthood and increasing the risk of cardiovascular mortality [5,9,17].…”
Section: Introductionmentioning
confidence: 99%